Crítica de Libros. J. M. de Miguel: La amorosa dictadura; Franz Kafka: La muralla china; Thomas Mann: Schopenhauer, Nietzsche, Freud. - José Luis Pedreira Massa (Asociacion Espanola de Neuropsiquiatria, 1985)
Sin resumen.